Does the digital transformation of manufacturing improve the technological innovation capabilities of enterprises? Empirical evidence from China - Zang, Jinxiang; Teruki, Neilson; Ong, Sharon Yong Yee; Wang, Yan (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
At present, China’s manufacturing industry is urgently in need of a transition, as well as an upgrade from low- to high-end production. Concurrently, as digital technology continues to advance, the enterprise-level digital transformation is anticipated to emerge as a new “engine” driving technological innovation. This study is centered on China’s A-share listed manufacturing enterprises, as we aim to explore the impact of digital transformation on technological innovation. Employing a fixed-effect model, the instrumental variable method, and propensity score matching, combined with a difference-in-differences approach, threshold regression, and a quantile regression model, we empirically examine the influence of digital transformation on technological innovation within the manufacturing sector. Our findings reveal the following: (1) Digital transformation enhances technological innovation. (2) Mediation analysis indicates that digital transformation boosts technological innovation by mitigating cost stickiness. (3) The heterogeneity analysis shows that the effect of digital transformation on technological innovation is more pronounced in larger enterprises, particularly those with lower technological intensity, lower asset intensity, and stronger innovation capabilities. The outcome of this study provides a decision-making reference for governments and enterprises, whereby the government can formulate industrial and fiscal policies, as well as helping enterprises to carry out digital transformation through policy guidance and support. Enterprises can formulate differentiated transformation strategies based on their own characteristics, optimize their cost structure through digital transformation, release resources for technological innovation, and improve their own technological innovation capabilities.